2020
DOI: 10.1177/1938640020952301
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Outcomes From Foot and Ankle Arthrodesis and Open Reduction and Internal Fixation Using Cellular Bone Allograft Augmentation

Abstract: Background ViviGen is an allogeneic cellular bone matrix product containing lineage-committed bone cells, and can be used as an alternative to autograft bone or other augments to aid in arthrodesis or to enhance bony healing in open reduction and internal fixation (ORIF) procedures. Methods This study included 153 consecutive patients undergoing ankle, midfoot, or hindfoot arthrodesis or ORIF procedures from January 2017 to October 2018, in which an allogeneic cellular bone matrix product was used to aid in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“… 2 , 16 , 27 Biological augmentation of arthrodesis in foot and ankle surgery using allogenic bone shows satisfying results and high fusion rates without experiencing adverse events because of its osteoconductive potential. 24 , 33 Other bone augmentation materials such as demineralized bone matrix (DBM) consisting of a collagen scaffold and several growth factors, most importantly bone morphogenetic proteins, result in a high positive turnover. 35 Thus, DBM can actively induce bone formation by its osteoinductive potential following endochondral ossification because of the recruitment of mesenchymal stem cells from bone.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 16 , 27 Biological augmentation of arthrodesis in foot and ankle surgery using allogenic bone shows satisfying results and high fusion rates without experiencing adverse events because of its osteoconductive potential. 24 , 33 Other bone augmentation materials such as demineralized bone matrix (DBM) consisting of a collagen scaffold and several growth factors, most importantly bone morphogenetic proteins, result in a high positive turnover. 35 Thus, DBM can actively induce bone formation by its osteoinductive potential following endochondral ossification because of the recruitment of mesenchymal stem cells from bone.…”
Section: Introductionmentioning
confidence: 99%
“…V-BC within the bone matrix do not stain positive for MHCII, suggesting V-BC are nonimmunogenic and providing an explanation of the lack of immune cell activation in the MLR assay. 10 × magnification; insets show magnified area of stained bone matrix several studies have demonstrated success using VBA in patients with comorbidities (Moran et al 2020;Roukis 2018;Roukis and Samsell 2018;Roukis et al 2020). In particular, Moran, et al (2020) reported an 86% fusion rate in 135 high-risk patients, which was similar to fusion rates reported with the use of autograft (Lareau 2015; Muller 2013).…”
Section: Discussionmentioning
confidence: 99%
“…10 × magnification; insets show magnified area of stained bone matrix several studies have demonstrated success using VBA in patients with comorbidities (Moran et al 2020;Roukis 2018;Roukis and Samsell 2018;Roukis et al 2020). In particular, Moran, et al (2020) reported an 86% fusion rate in 135 high-risk patients, which was similar to fusion rates reported with the use of autograft (Lareau 2015; Muller 2013). Likewise, in spinal fusion, in addition to patient comorbidities and lifestyle risk factors, the number of levels to be fused can add to the complexity of a case and potentially limit the ability to achieve successful fusion.…”
Section: Discussionmentioning
confidence: 99%
“…By providing all 3 essential bone remodeling properties, VF-CBA facilitated fusion at the defect site. Although VF-CBA has been used successfully to achieve fusion in spine and orthopedic applications, [13][14][15][16][17][18] its use in oral and maxillofacial surgery is an emerging application, [19][20][21] and in particular, to our knowledge, has not yet been shown in a pediatric patient. Therefore, this is the first known report of a successful immediate reconstruction of a large segmental mandibular defect using VF-CBA in a young child.…”
Section: Discussionmentioning
confidence: 99%